Silent Synapse-Based Mechanisms of Critical Period Plasticity - Xu, Weifeng; Löwel, Siegrid; Schlüter, Oliver M. (Frontiers in Cellular Neuroscience, 2020)
Critical periods are postnatal, restricted time windows of heightened plasticity in cortical neural networks, during which experience refines principal neuron wiring configurations. Here, we propose a model with two distinct types of synapses, innate synapses that establish rudimentary networks with innate function, and gestalt synapses that govern the experience-dependent refinement process. Nascent gestalt synapses are constantly formed as AMPA receptor-silent synapses which are the substrates for critical period plasticity. Experience drives the unsilencing and stabilization of gestalt synapses, as well as synapse pruning. This maturation process changes synapse patterning and consequently the functional architecture of cortical excitatory networks. Ocular dominance plasticity (ODP) in the primary visual cortex (V1) is an established experimental model for cortical plasticity. While converging evidence indicates that the start of the critical period for ODP is marked by the maturation of local inhibitory circuits, recent results support our model that critical periods end through the progressive maturation of gestalt synapses. The cooperative yet opposing function of two postsynaptic signaling scaffolds of excitatory synapses, PSD-93 and PSD-95, governs the maturation of gestalt synapses. Without those proteins, networks do not progress far beyond their innate functionality, resulting in rather impaired perception. While cortical networks remain malleable throughout life, the cellular mechanisms and the scope of critical period and adult plasticity differ. Critical period ODP is initiated with the depression of deprived eye responses in V1, whereas adult ODP is characterized by an initial increase in non-deprived eye responses. Our model proposes the gestalt synapse-based mechanism for critical period ODP, and also predicts a different mechanism for adult ODP based on the sparsity of nascent gestalt synapses, as substrates for critical period plasticity. Under our model, early life experience shapes the boundaries (the gestalt) for network function, both for its optimal performance as well as for its pathological state. Thus, reintroducing nascent gestalt synapses as plasticity substrates into adults may improve the network gestalt to facilitate functional recovery.